2012
DOI: 10.1016/j.jpba.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

HPLC–MS method for the simultaneous quantification of the antileukemia drugs imatinib, dasatinib and nilotinib in human peripheral blood mononuclear cell (PBMC)

Abstract: A new method using high performance liquid chromatography coupled with electrospray mass spectrometry is described for the quantification of PBMC concentration of tyrosine kinase inhibitors imatinib, dasatinib and nilotinib. A simple PBMC isolation and extraction procedure were applied on 10-14 mL of blood aliquots. Chromatographic separation of drugs and Internal Standard (quinoxaline) was achieved with a gradient (acetonitrile and water + formic acid 0.05%) on a C18 reverse phase analytical column with 25 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 60 publications
0
37
0
1
Order By: Relevance
“…The correlation of imatinib intracellular concentration in bone marrow cells of CML patients with therapeutic response has also been shown by Zhong et al (2012). Widmer et al (2006) andD'Avolioa et al (2012) observed in PBMĆ s an intra/extracellular concentration ratio of approximately 8, confirming the active uptake of the drug into these cells.…”
Section: Introductionmentioning
confidence: 54%
“…The correlation of imatinib intracellular concentration in bone marrow cells of CML patients with therapeutic response has also been shown by Zhong et al (2012). Widmer et al (2006) andD'Avolioa et al (2012) observed in PBMĆ s an intra/extracellular concentration ratio of approximately 8, confirming the active uptake of the drug into these cells.…”
Section: Introductionmentioning
confidence: 54%
“…The extraction procedure based on protein precipitation is simple, rapid and economic; instead of procedures used by other methods that requires an extensive sample preparation: for example, Varshney extracted samples on solid-phase extraction cartridges, which is a long and expensive procedure [23]; other methods use toxic solvents (methy t-butyl ether, diethyl ether) as extraction solutions, that are difficult to use in clinical routine [24,25]. Despite its chemical structure difference to those of the other analytes, the internal standard quinoxaline is cheap and easy to purchase, more than sildenafil-d8 and N-desmethyl sildenafil-d8 [25]; and it was used in many our other chromatographic published methods [26][27][28][29][30][31][32][33][34][35][36]. Furthermore, its matrix effect and recovery are very close to those of sildenafil and its metabolite, making it a good choice as internal standard.…”
Section: Discussionmentioning
confidence: 99%
“…Parise et al described an HPLC-mass spectrometry (MS) method for NTB in plasma and serum [7]. Furthermore, simultaneous assay of NTB with other antichronic myeloid leukemia drugs using solid phase extraction and ultra-performance liquid chromatographytandem mass (UPLC-MS/MS) [8], HPLC-UV [9][10], HPLC-MS/MS [11][12][13][14][15], and HPLC-MS [16,17] have been reported.…”
Section: Nilotinib (Ntb) [4-methyl-n-[3-(4-methyl-1h-imidazol-1-yl)-5mentioning
confidence: 99%